Overview of systematic reviews on Chinese patented oral medicines for promoting blood circulation and removing blood stasis combined with western medicine in the treatment of coronary heart disease angina pectoris - Xinyi Chen; Huan Liu; Hongli Wu; Yi Deng; Wenxi Peng; Yanming Xie; Junjie Jiang (Frontiers in Cardiovascular Medicine)
ObjectiveTo evaluate the methodology quality, reporting quality, and evidence quality of systematic reviews and meta-analyses on Chinese patented oral medicines that promote blood circulation and remove blood stasis combined with conventional Western medicine in the treatment of coronary heart disease angina pectoris. The aim is to identify and address methodological issues in systematic reviews of Chinese patented oral medicines for promoting blood circulation and removing blood stasis in angina pectoris. This study also offers methodological guidance for future research design and implementation, and provides a basis for clinical decision-making.MethodsA systematic search was performed using CNKI, Wanfang, VIP, CBM, PubMed, Cochrane Library, Embase, and Web of Science databases, covering the period from the inception of each database to July 18, 2024, and meta-analyses on randomized controlled trials were included. Methodological quality was evaluated using AMSTAR-2, reporting quality using PRISMA 2020, and evidence quality of the outcome indicators using GRADE.ResultsTwenty meta-analyses were examined, involving a total of 41,231 patients with angina pectoris. The methodological quality of all studies was rated as “critically low,” with notable deficiencies in the registration of the study protocol, study inclusion criteria, assessment of individual study risk of bias, evaluation of the likelihood of publication bias, and discussion of the effects of publication bias on the results. The assessment of the three qualities mentioned above revealed common issues, including incomplete abstracts, lack of characteristics for pooled outcomes, failure to report risk of bias across studies, missing registration information, lack of accessibility details for protocols, and unreported modifications to registered protocols or plans. Evidence quality assessment revealed that 16 outcome indicators were rated as “moderate,” 29 as “low,” and 46 as “very low.”ConclusionDespite the demonstrated efficacy and safety of Chinese patented oral medicines that promote blood circulation and remove blood stasis in the adjuvant treatment of angina pectoris, the low methodological and reporting quality of current systematic reviews and meta-analyses compromises the reliability of these findings. Future research should focus on standardizing study design and reporting to improve the reliability of evidence.